Optimization of mechanical properties, biocorrosion properties and antibacterial properties of as-cast Ti–Cu alloys. (21st October 2016) - Zhang, Erlin; Ren, Jing; Li, Shengyi; Yang, Lei; Qin, Gaowu
Abstract: Ti–Cu sintered alloys have shown good antibacterial abilities. However, the sintered method (powder metallurgy) is not convenient to produce devices with a complex structure. In this paper, Ti–Cu alloys with 2.0, 3.0 and 4.0 wt.% Cu were prepared in an arc melting furnace and subjected to different heat treatments: solid solution and ageing, to explore the possibility of preparing an antibacterial Ti–Cu alloy by a casting method and to examine the effect of Cu content. Phase identification was conducted on an XRD diffraction meter, and the microstructure was observed by a metallographic microscope, a scanning electron microscope (SEM) with energy disperse spectroscopy (EDS) and transmission electron microscopy (TEM). Microhardness and the compressive property of Ti–Cu alloys were tested, and the corrosion resistance and antibacterial activity were assessed in order to investigate the effect of the Cu content. Results showed that the as-cast Ti–Cu alloys exhibited a very low antibacterial rate against Staphylococcus aureus ( S. aureus ). Heat treatment improved the antibacterial rate significantly, especially after a solid and ageing treatment (T6). Antibacterial rates as high as 90.33% and 92.57% were observed on Ti–3Cu alloy and Ti–4Cu alloy, respectively. The hardness, the compressive yield strength, the anticorrosion resistance and the antibacterial rate of Ti–Cu alloys increased with an increase of Cu content in all conditions. It was demonstrated that homogeneous distribution and a fine Ti2 Cu phase played a very important role in the mechanical property, anticorrosion and antibacterial properties. Furthermore, it should be pointed out that the Cu content should be at least 3 wt.% to obtain good antibacterial properties (>90% antibacterial rate) as well as satisfactory mechanical properties.